An RNA-seq-Based Expression Profiling of Radiation-Induced Esophageal Injury in a Rat Model. Issue 2 (3rd May 2019) - Sun, Zhiqiang; Li, Jinhui; Lin, Min; Zhang, Shuyu; Luo, Judong; Tang, Yiting
Radiation-induced acute injury is the main reason for the suspension of radiotherapy and unsuccessful treatment of cancer. It is of great importance to understand the molecular mechanism of radiation-induced esophageal injury. We used RNA-seq data from normal esophageal tissue and irradiated esophageal tissues and applied computational approaches to identify and characterize differentially expressed genes and detected 40 059 messenger RNAs (mRNAs) previously annotated and 717 novel long noncoding RNAs (lncRNAs). There were 14 upregulated and 32 downregulated lncRNAs among the differentially expressed lncRNA group. Their target genes were involved in the mRNA surveillance pathway, pathological immune responses, and cellular homeostasis. Additionally, we found 853 differentially expressed mRNAs, and there were 384 upregulated and 469 downregulated mRNAs. Notably, we found that the differentially expressed mRNAs were enriched for steroid biosynthesis, the tumor necrosis factor signaling pathway, focal adhesion, pathways in cancer, extracellular matrix–receptor interaction, and so on. The response of normal esophageal tissues to ionizing radiation is multifarious. The radiation-induced cell damage response by multiple pathways followed by pathological immune responses activated. Studies on the dynamic network of molecules involved in radiation-induced esophageal injury are under way to clarify the regulatory mechanisms and identify the candidate targets.